Comparison of spark channel expansion in hydrogen, oxygen and nitrogen - Korytchenko, K.V.; Kashanskyi, Yu.V.; Cherkashyn, O.V.; Belyuchenko, D.Yu.; Maksimov, A.V.; Nikorchuk, A.I.; Chernenko, P.V. (Вопросы атомной науки и техники, 2020)
The results of the spark channel expansion simulation in various gases such as hydrogen, oxygen and nitrogen have been presented. Difference in thermodynamic properties of the various gases has been taken into account. Influence of a type of gas on the discharge current, the spark resistance, the energy deposited in the spark and the spark gas-dynamic expansion has been found out. Influence of initial species concentration in mixture of nitrogen, hydrogen and oxygen on detonation initiation by spark discharge has been discussed. Представлені результати моделювання розширення іскрового каналу в різних газах, таких як водень, кисень і азот. Враховано відмінність y термодинамічних властивостях різних газів. Виявлено вплив типу газу на розрядний струм, іскровий опір, енергію, вкладену в іскру, і газодинамічне розширення іскри. Обговорено вплив початкової концентрації частинок y суміші азоту, водню і кисню на ініціювання детонації іскровим розрядом. Представлены результаты моделирования расширения искрового канала в различных газах, таких как водород, кислород и азот. Учтено различие в термодинамических свойствах различных газов. Выявлено влияние типа газа на разрядный ток, искровое сопротивление, энергию, вложенную в искру, и газодинамическое расширение искры. Обсуждено влияние начальной концентрации частиц в смеси азота, водорода и кислорода на инициирование детонации искровым разрядом.